PENGARUH GROWTH OPPORTUNITY, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Pratiwi, Dyah Putri; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Firm value can be very important on a go public company. Firm value is the reflection of the rate of financial performance of the company. The fluctuation of firm value can give influence to the point of view of investors to the company. This research is meant to test growth opportunity, profitabilty and firm size to the firm value.The population is all manufacturing companies wich are listed in Indonesia Stock Exchange in 2012â 2014 periods and it has been carried out by using audited financial statement whice has been obtained by using purposive sampling and predetermined criteria. Therefore 44 manufacturing companies whice have met the research criteria have been selected as samples. The analyse and SPSS (Statistical Product and Service Solution). It can be concluded from the result of the research that : 1) Growth Opportunity does not have any influence to the firm value; 2) profitability gives influence to the firm value; 3) firm size give influence to the firm value.Keywords : Growth opportunity, profitability, size, firm value